Entre flores, espinhos e cruz: etnografia de uma comunidade terapêutica feminina em Imperatriz/MA - NASLAUSKY, Ana Luísa Rocha Martins (2021)
The expansion of therapeutic communities (TCs) is present in the debate about models of care for people who make problematic use of psychoactive substances. The TCs’s therapeutic practices work towards the ideal of abstinence, reinforcing a prohibitionist political model, with historical roots in the American protestant moralism of the last centuries. The reception of women in TCs articulates some topics related to gender. In order to identify which gender representations are and how they operate in understanding of the institutional and religious environment of a TC with exclusive reception for women, an ethnographic research was proceed at CT Renascer Feminino, administered by an evangelical church in Imperatriz /MA. A bibliographic review was also made, in books and articles, for theoretical understanding of the theme. Throughout the research, it was found that the researched TC, having religious discourse as its background, is based on some gender representations in the execution of its practices, involving motherhood, affective relationships, appearance and body care, work, sexuality, among others.